Studying the changes of corneal endothelium cells in patients with spherical refractive errors - Dalloul, Azdasheer Mofied; Suleiman, Yusuf Mohammed; Krdoghly, Najwa Fayez (Journal of medical and pharmaceutical sciences, 2022)
Objective: To study of the relationship between spherical refractive errors and the changes in corneal endothelial cells. Methods: This sectional study, 1098 eyes of 663 persons attending the ophthalmological clinic at Tishreen University Hospital were studied between the years 2020-2021, they were divided into three groups according to the spherical equivalent value (193 nearsighted, 254 partially sighted, 216 long sighted), and also each was divided into three groups according to the value of the spherical equivalent. From the farsightedness and myopia groups to groups according to the severity of the refraction present (mild, moderate, severe), all participants underwent a complete ophthalmological examination including corneal endothelial cell counts by Endothelium Mic. Non contact, Specular Microscope, where the average of three successive measurements of endothelial cell density (MCD), coefficient of variation (CV) for cell volume, and hexogram (EX%) were taken. Results: The values of endothelial cell density (MCD) (P ˂ 0.05) and hexameric cell percentage (EX%) (P ˂ 0.05) decreased statistically significantly, while the value of the covariance (CV) increased (P ˂ 0.05) with increasing myopia, This change was at the expense of moderate myopia and severe myopia, while mild myopia did not have a statistically significant effect, as well as for hyperopia, where we did not find significant statistical differences in the three variables (MCD) (EX%) (CV) (P ˃ 0.05). Conclusion: Hyperopia does not affect the endothelial cells of the cornea, while moderate to severe myopia causes a significant change in the endothelial cells of the cornea.